Bioturbation by endogeic earthworms facilitates entomopathogenic nematode movement toward herbivore‑damaged maize roots - Fattore, Sandrine; Xiao, Zhenggao; Godschalx, Adrienne; Röder, Gregory; Turlings, Ted; Le Bayon, Renée-Claire; Rasmann, Sergio (My University, 2020)
Entomopathogenic nematodes (EPNs) have been extensively studied as potential biological control agents against root-feeding crop pests. Maize roots under rootworm attack have been shown to release volatile organic compounds, such as (E)-β-caryophyllene (Eβc) that guide EPNs toward the damaging larvae. As yet, it is unknown how belowground ecosystems engineers, such as earthworms, affect the biological control capacity of EPNs by altering the root Eβc-mediated tritrophic interactions. We here asked whether and how, the presence of endogeic earthworms affects the ability of EPNs to find root-feeding larvae of the beetle Diabrotica balteata. First, we performed a field mesocosm experiment with two diverse cropping systems, and revealed that the presence of earthworms increased the EPN infection potential of larvae near maize roots. Subsequently, using climatecontrolled, olfactometer-based bioassays, we confirmed that EPNs response to Eβc alone (released from dispensers) was two-fold higher in earthworm-worked soil than in earthworm-free soil. Together our results indicate that endogeic earthworms, through burrowing and casting activities, not only change soil properties in a way that improves soil fertility but may also enhance the biocontrol potential of EPNs against root feeding pests. For an ecologically-sound pest reduction in crop fields, we advocate agricultural practices that favour earthworm community structure and diversity.